2022
DOI: 10.24002/ijis.v4i2.5449
|View full text |Cite
|
Sign up to set email alerts
|

Game Design Factor Questionerin User Experience Analysis on Selera Nusantara Game

Abstract: Game products are one of the media to provide pleasure, satisfaction and knowledge for users. Game Selera Nusantara is a game product created by a game studio in Yogyakarta, namely Gambir Studio, created with the aim of providing pleasure, satisfaction and knowledge to its users. In order for the goal of the Selera Nusantara Game to be achieved, a game design by a user-centered game designer is needed. Game Selera Nusantara is a game with the Casual genre that has a target audience of children and teenagers wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
0
0
0
Order By: Relevance
“…Other factors analyzed included Goals, Game Mechanism, Interaction, Fantasy Game, Narrative, Sensation, and Game Value. The results showed that games about Indonesian culture are very good in terms of user experience [24].…”
Section: B State Of the Artmentioning
confidence: 98%
See 1 more Smart Citation
“…Other factors analyzed included Goals, Game Mechanism, Interaction, Fantasy Game, Narrative, Sensation, and Game Value. The results showed that games about Indonesian culture are very good in terms of user experience [24].…”
Section: B State Of the Artmentioning
confidence: 98%
“…All required question data were entered using Google Forms and distributed to students using the link. The question is taken from software quality testing [24]. The factors that influence game quality are Functionality, Reliability, Portability, Usability, Efficiency, and Maintainability [16], as listed in Table 1.…”
Section: A Research Questionnairementioning
confidence: 99%
“…Arknights bisa bersaing seperti ini meskipun dia adalah game Tower Defense, dikarenakan user experience nya [3], [4], [13]- [15]. Apa yang membuat banyak para player Arknights bisa betah memainkan game ini sampai sekarang tentunya berasal dari pengalaman mereka saat pertama kali bermain Arknights.…”
Section: Pendahuluanunclassified
“…Thus, the findings of Kavakli and Thorne (2002) emphasized the significance of usability testing and input device selection to enhance the gaming experience. Regarding user experience evaluations, Widhiyanti et al (2022) reviewed the use of the Game Design Factor Questionnaire in evaluating the user experience of the Selera Nusantara Game, which introduces the Nusantara culture. The study found that the game received high scores in various factors, including game goals, mechanism, interaction, fantasy, narrative, sensation, and value.…”
Section: Influencing Factors Of Gaming Mouse and Experiencementioning
confidence: 99%
“…The study found that the game received high scores in various factors, including game goals, mechanism, interaction, fantasy, narrative, sensation, and value. Accordingly, the study conducted by Widhiyanti et al (2022) emphasized the importance of user experience in game design and provides effective methods for evaluating and improving it.…”
Section: Influencing Factors Of Gaming Mouse and Experiencementioning
confidence: 99%